Handbook of distance learning for real-time and asynchronous information technology education - Negash 1960- (Information Science Reference, 2008)
"This book looks at solutions that provide the best fits of distance learning technologies for the teacher and learner presented by sharing teacher experiences in information technology education"--Provided by publisher